2022
DOI: 10.3389/fcimb.2022.989534
|View full text |Cite
|
Sign up to set email alerts
|

Carbohydrate-binding protein from stinging nettle as fusion inhibitor for SARS-CoV-2 variants of concern

Abstract: Urtica dioica agglutinin (UDA) is a carbohydrate-binding small monomeric protein isolated from stinging nettle rhizomes. It inhibits replication of a broad range of viruses, including coronaviruses, in multiple cell types, with appealing selectivity. In this work, we investigated the potential of UDA as a broad-spectrum antiviral agent against SARS-CoV-2. UDA potently blocks transduction of pseudotyped SARS-CoV-2 in A549.ACE2+-TMPRSS2 cells, with IC50 values ranging from 0.32 to 1.22 µM. Furthermore, UDA preve… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 60 publications
2
13
0
Order By: Relevance
“…On this basis, it may be proposed that multivalent targeting of key glycans on SARS-CoV-2 Spike improves the chances of avoiding facile mutational escape by the virus. Indeed, the substantial breadth of lectin antiviral effects observed in this current work and elsewhere (16,(51)(52)(53)(54)(55) for variants of SARS-CoV-2 supports this expectation. Furthermore, the antiviral effects observed with a fully infectious coronavirus that is not in the SARS-CoV-2 line argues for a potential broad spectrum anti-coronavirus activity as has been previously reported for GRFT in an investigation of its activity against SARS-CoV-1 (56).…”
Section: Discussionsupporting
confidence: 81%
“…On this basis, it may be proposed that multivalent targeting of key glycans on SARS-CoV-2 Spike improves the chances of avoiding facile mutational escape by the virus. Indeed, the substantial breadth of lectin antiviral effects observed in this current work and elsewhere (16,(51)(52)(53)(54)(55) for variants of SARS-CoV-2 supports this expectation. Furthermore, the antiviral effects observed with a fully infectious coronavirus that is not in the SARS-CoV-2 line argues for a potential broad spectrum anti-coronavirus activity as has been previously reported for GRFT in an investigation of its activity against SARS-CoV-1 (56).…”
Section: Discussionsupporting
confidence: 81%
“…Lectins are characterized by their reversible binding to a specific mono-or oligosaccharide [25]. Several lectins have been reported to exert anti-bacterial and antiviral activities [13,14,26] and some lectins have been shown to elicit antiviral activity by binding with viral glycans of enveloped viruses [15][16][17][18][19] such as HIV and SARS-CoV2. Here, in contrast, we found that the mechanism by which UDA inhibits RABV infection stems primarily from an interaction with the host cells.…”
Section: Discussionmentioning
confidence: 99%
“…HHA, a mannose specific lectin from Hippeastrum Hybrid has been reported to inhibit SARS-CoV at the stage of viral attachment and fusion [18]. UDA, a N-acetylglucosamine specific lectin from Urtica dioica inhibits SARS-CoV-2 infection of cells by binding to the spike protein [19]. Some lectins were shown to reduce infection of cells with the RABV [20,21].…”
Section: Introductionmentioning
confidence: 99%
“… Atienza et al, 2006 , Cerutti et al, 2022 , Chan, 2022 , Cui et al, 2022 , Duan et al, 2022 , Feng et al, 2017 , Giaever and Keese, 1984 , Hoffmann et al, 2020 , Iwata-Yoshikawa et al, 2022 , Jafary et al, 2021 , Kilby et al, 1998 , Koch et al, 2021 , Lan et al, 2022 , Laporte et al, 2021 , Lozada et al, 2021 , Meng et al, 2022 , Montefiori, 2009 , Ngoc Le et al, 2019 , Nguyen et al, 2020 , Oeyen et al, 2022 , Ou et al, 2020 , Pennington and Van de Walle, 2017 , Poumbourios et al, 1999 , Shang et al, 2020 , Stupin et al, 2021 , Suzuki et al, 2022 , Tang et al, 2020 , Vanderheijden et al, 2021 , Vanhulle et al, 2022a , Vanhulle et al, 2022b , Vanhulle et al, 2022c , Walls et al, 2020 , Watterson et al, 2016 , Wrapp et al, 2020 , Xia et al, 2020 , Xu et al, 2016 , Xu et al, 2021 , Zhang et al, 2021 , Zhao et al, 2021 , Zhao et al, 2021 .…”
Section: Uncited Referencesmentioning
confidence: 99%
“…In previous studies (23,24), we demonstrated that SARS-CoV-2 viral entry can be mimicked by a cell-cell fusion system in which acceptor cells express the cellular human ACE2 receptor and donor cells the complementary viral spike protein. In our current work, the lung epithelial cell line A549 (stably transduced with human ACE2 to elevate the endogenous receptor level) was chosen as acceptor cell, whereas spiketransfected HEK293T cells were selected as donor cells because of the high plasmid transfection efficiency of the latter.…”
Section: Sars-cov-2 Spike-induced Cell-cell Fusionmentioning
confidence: 99%